First, eliminate the parenthesis by multiplying each term within the parenthesis by the term outside the parenthesis:
color(red)(sqrt(5))(3 + sqrt(15)) =>
(color(red)(sqrt(5)) * 3) + (color(red)(sqrt(5)) * sqrt(15)) =>
3sqrt(5) + (sqrt(5) * sqrt(15))
Next, use this rule for multiplying radicals to rewrite the term on the right:
sqrt(color(red)(a)) * sqrt(color(blue)(b)) = sqrt(color(red)(a) * color(blue)(b))
3sqrt(5) + (sqrt(color(red)(5)) * sqrt(color(blue)(15))) =>
3sqrt(5) + (sqrt(color(red)(5) * color(blue)(15))) =>
3sqrt(5) + sqrt(75)
Then, we can use the same rule in reverse to again rewrite and simplify the term on the right:
3sqrt(5) + sqrt(75) =>
3sqrt(5) + sqrt(color(red)(25) * color(blue)(3)) =>
3sqrt(5) + (sqrt(color(red)(25)) * sqrt(color(blue)(3))) =>
3sqrt(5) + (5 * sqrt(color(blue)(3))) =>
3sqrt(5) + 5sqrt(3)